Shariah Governance Framework for Islamic Banking Institutions (IBIs): A Critical Analysis - Abbasi, Abdus Sattar (Islamic Banking and Finance Review, 2020)
The purpose of the current study is to critically analyse the Shariah Governance Framework (SGF 2018) of the State Bank of Pakistan (SBP). SGF 2018 provides the foundation for the operations of the Islamic Banking Institutions (IBIs) in Pakistan. The requirement of Shariah compliance along with the compliance of the contemporary banking standards makes it more challenging for the staff of the IBIs to ensure the satisfaction of all stakeholders. Besides profitability, the clientele of the IBIs needs complete satisfaction regarding the fact that their funds are administered according to the Shariah laws and returns are generated only from the business operations permissible in the Shariah. SGF 2018 was critically analysed by systematically and objectively identifying its special characteristics relevant for the IBIs. Moreover, utilising the interpretive and naturalistic approaches including both observational and narrative based discourses associated with ground realities, the current study outlines pragmatic modifications in the existing framework to bridge the gap between the Shariah Board (SB) and the Board of Directors (BOD). Over the years, Shariah governance mechanisms have evolved significantly in Pakistan. However, there is always the need and room for improvement and further development. SGF enables the smooth functioning of the IBIs with a predetermined set of instructions and objectives. Nevertheless, the IBIs need continuous monitoring and handholding to implement the SGF in its true letter and spirit. The current study critically analysed the SBP’s updated SGF 2018 through content analysis and identified some important gaps in it. These gaps include the absence of the Board’s Committee of Shariah Governance (BCSG) and the lack of attention towards Shariah compliance. Furthermore, the ratings of the IBIs were investigated and discussed with reasonable clarity. It was observed that the lack of performance evaluation of the BODs and the SBs is an important impediment in the development and expansion of the IBIs. The current study identified that the existing SGF is devoid of determining the key performance indicators (KPIs) for the IBIs in terms of their Shariah compliance as well as the performance of their respective BODs and SBs. Therefore, the study proposed a new SGF for the IBIs to ensure a clos liaison between their respective BODs and SBs through the existing BCSG, along with the provision of the KPIs required for gauging their Shariah compliance rating.